Efficacy of melatonin as an adjunct to first-line therapy in epileptic patients. - Safiullah; Sadia Riaz (The Professional Medical Journal, 2026)
Objective: To determine the efficacy of melatonin as an adjunct to first-line antiepileptic therapy in reducing seizure severity, seizure frequency, and electroencephalographic (EEG) abnormalities in pediatric patients with generalized epilepsy. Study Design: Quasi-experimental Comparative study. Setting: Department of Pediatrics, Pakistan Institute of Medical Sciences (PIMS), Islamabad. Period: July 2025 to Dec 2025. Methods: A total of 60 children aged 2–12 years with generalized epilepsy and suboptimal seizure control despite first-line antiepileptic therapy were enrolled using consecutive sampling. Patients were allocated into two groups: the treatment group (n=30) received melatonin as an adjunct to first-line therapy, while the control group (n=30) received placebo with first-line therapy. Melatonin was administered at bedtime for 12 weeks (1 mg for children